The quality improvement handbook - Bauer, John. (Milwaukee, Wis. ASQ Quality Press, 2006)
The use of quality and continual improvement is no longer considered the sole property of manufacturing or of the traditional engineering and production environment. Most professionals entering the workforce today are required to analyze situations, identify problems, and provide solutions for improved performance. Improving the organization is everyone?s job. Teamwork is critical, requiring the participation of members of all backgrounds, nationalities, educational levels, and career aspirations. This book is for anyone who wants to improve themselves and/or their organization. It is particularly salient for those at the beginning stages of learning about the history, concepts, and tools of quality. In addition, the content of this book is structured exactly to follow the Body of Knowledge (BoK) of ASQ's Certified Quality Improvement Associate (CQIA) certification. While the content coincides with the sequence of the BoK, each chapter stands alone, and the chapters may be read in any order. Where appropriate, supplemental reading suggestions are provided. A sample test is provided on a CD-ROM, along with tables giving cross-references to the suggested reference materials as well as the BoK. Answers to the questions in the sample test are also provided. Contents: Part I Quality Basics 1 A. Terms, Concepts, and Principles 2 B. Benefits of Quality, C. Quality Philosophies Part II Teams 3 A. Understanding Teams 4 B. Roles and Responsibilities 5 C. Team Formation and Group Dynamics Part III Continuous Improvement 6 A. Incremental and Breakthrough Improvement 7 B. Improvement Cycles 8 C. Problem Solving Process 9 D. Improvement Tools 10 E. Customer-Supplier Relationships Appendices A. ASQ Certified Quality Improvement Associate Body of Knowledge B. ASQ Code of Ethics C. Quality Glossary D. Additional Reading E. Practice Questions and Answers, Cross-References (CD-ROM)
Includes bibliographical references and index.
Keywords: Quality control -Handbooks, manuals, etc